2023
DOI: 10.3390/ma16031140
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Dependence and Recrystallization Modeling for TC18 Alloy during Post-Deformation Annealing

Abstract: In this paper, the dependence of dynamic recrystallization (DRX) and post-dynamic recrystallization (PDRX) of TC18 alloy on strain rate within the range of 0.001 s−1~1 s−1 was investigated through isothermal compression and subsequent annealing in the single-phase region. Electron backscatter diffraction (EBSD) characterization was employed to quantify microstructure evolution and to reveal the recrystallization mechanism. At the thermo-deformation stage, the DRX fraction does not exceed 10% at different strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…The effect of the strain rate on GND characteristics is also remarkable. Li et al [21][22][23] and Cheng et al [24] demonstrated a positive correlation between GND density and the strain rate, during tensile deformation at low to medium strain rates and in compression experiments with the strain rate ranging from 1800 s −1 to 4200 s −1 , respectively. At even higher strain rates, Liu et al [25] discovered that the GND density increases significantly during extremely high-strain-rate impact in AISI 1045 steel.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of the strain rate on GND characteristics is also remarkable. Li et al [21][22][23] and Cheng et al [24] demonstrated a positive correlation between GND density and the strain rate, during tensile deformation at low to medium strain rates and in compression experiments with the strain rate ranging from 1800 s −1 to 4200 s −1 , respectively. At even higher strain rates, Liu et al [25] discovered that the GND density increases significantly during extremely high-strain-rate impact in AISI 1045 steel.…”
Section: Introductionmentioning
confidence: 98%